"Aggressive Refugees, Violent Hooligans, Concerned Citizens": Reinterpreting Multiple Processes of Difference-Making in Mediatizations of Migration and Conflict in East Germany in the German Media1. Issue 1 (2nd January 2021) - Trzeciak, Miriam Friz; Schäfer, Jana
Abstract: While feminist postcolonial literature provides valuable insight into the intersectional effects of race, gender and sexuality, other dimensions of difference-making like region or class often remain invisible. Combining postcolonial and post-socialist perspectives, this paper explores the intersections of multidimensional frontiers in the social production of "otherness". Using a sociology of knowledge approach to discourse, we analyze how current mediatizations of migration and conflict in East German cities link ethnosexual with spatio-cultural-historical frontiers . This interplay of multifaceted frontiers constitutes internal and external images of a cultural "other" and contributes to internal coherence within the sexually and racially imagined nation.